Structural basis of katanin p60:p80 complex formation. Issue 1 (December 2017) - Rezabkova, Lenka; Jiang, Kai; Capitani, Guido; Prota, Andrea; Akhmanova, Anna; Steinmetz, Michel; Kammerer, Richard
Abstract Interactions between microtubule (MT) interacting and trafficking (MIT) domains and their binding proteins are important for the accurate progression of many cellular processes that require the AAA+ ATPase machinery. Therefore, knowledge on the structural basis of MIT domain interactions is crucial for understanding the molecular mechanisms underlying AAA+ ATPase function. Katanin is a MT-severing AAA+ ATPase that consists of p60 and p80 subunits. Although, the hexameric p60 subunit is active alone, its association with the p80 subunit greatly enhances both the MT-binding and -severing activities of katanin. However, the molecular mechanism of how the p80 subunit contributes to katanin function is currently unknown. Here, we structurally and functionally characterized the interaction between the two katanin subunits that is mediated by the p60-MIT domain and the p80 C-terminal domain (p80-CTD). We show that p60-MIT and p80-CTD form a tight heterodimeric complex, whose high-resolution structure we determined by X-ray crystallography. Based on the crystal structure, we identified two conserved charged residues that are important for p60-MIT:p80-CTD complex formation and katanin function. Moreover, p60-MIT was compared with other MIT domain structures and similarities are discussed.